Analisis Supply Chain Management Pabrik Tahu Nasional Kota Madiun Menggunakan Metode Economic Order Quantity - Syifa Dida Batista; Danil Irdan; Rangga Bayu Anggoro; Aloysius Tommy Hendrawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Every company that carries out production activities needs a supply of raw materials. With the availability of raw materials, it is hoped that industrial companies can carry out the production process according to consumer demand. In addition, adequate supplies of raw materials in the warehouse are also expected to improve the smoothness of production or service to consumers, as well as prevent shortages of raw materials. This research aims to identify and analyze the inventory management of raw materials implemented by the National Tofu Factory. The research method used is descriptive, with analysis using the Economic Order Quantity (EOQ) method. The data collected is in the form of interview results as primary data. The results of the research show that the management of raw material inventory by the National Tofu Factory has not been optimal. Based on the EOQ calculation, the amount of existing raw material inventory is smaller than what is recommended by the EOQ method. Therefore, additional raw material supplies are needed to support the smooth production process. The National Tofu Factory is also advised to provide adequate warehouses to store raw material supplies, especially for soybeans, so that they can accommodate more raw materials and reduce ordering costs.